Pengembangan Aplikasi Pencarian Film (Rekonifi) Dengan Metode Vector Space Model (VSM) Berbasis Android - Imron Hari Budisetyo; Adam Hendra Brata; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
At the end of 2016, indonesian film industry has improved again. The number of film audiences in Indonesia increased to 69.3 million people, differently six years ago. Increase occurred in the number of movies in theaters too. Its 99 movies in 2013. However, increasing the number of films will make the audience confused to choose the movie what they want. The authors conducted a survey with 30 respondents related habit of viewers to search of movie data on search sites, but 19 respondents said the data is inaccurate. In searching by 12 respondents, the keyword used is description of the movie, so this way is the right way to get a movie title. With this background, the author build a movie search application with Vector Space Model (VSM) method to make easier for viewers search the movie recommendations based on the synopsis of stories. Implementation with Unity as engine. Accuracy testing is done with 100% result. It is by entering the synopsis as keyword and the results obtained in the form of a movie title like synopsis input. Manual calculations performed on one of movie titles and have result value of 0.956. Its means VSM can find similarity of keyword data with the description of the movie.